(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To assess the level of adherence and the quality of bowel cleansiness before colonoscopy at the Gastroenterology and Hepatology Center, Bach Mai Hospital. Method: A cross-sectional study was conducted on 308 patients at the Gastroenterology and Hepatology Center, Bach Mai Hospital, Hanoi, from July to September 2025. The Chi-square test and Fisher’s Exact test were used to evaluate differences in patient attitudes, adherence, and quality of bowel preparation. Results: The study demonstrated that both bowel preparation regimens achieved a standard quality, as assessed by the Boston Bowel Preparation Scale. The same-day regimen had a higher Boston score (96.2% vs. 94.2%) but was associated with more symptoms of dizziness and nausea (59.6% vs. 31.8%). Conclusion: Both bowel preparation regimens provided equivalent cleansing quality and met the requirements for colonoscopy. The same-day regimen showed a higher Boston score but more adverse symptoms, whereas the split-dose regimen from the previous day offered better comfort despite a longer preparation time. Enhancing patient experience to improve bowel preparation plays a crucial role in detecting and diagnosing patients.